Sustainable bioenergy : advances and impacts - Rai, Mahen; Ingle, Avinash P. (Elsevier, 2019)
Sustainable Bioenergy: Advances and Impacts presents a careful overview of advances and promising innovation in the development of various bioenergy technologies. It covers the production of bio-jet fuel, algal biofuels, recent developments in bioprocesses, nanotechnology applications for energy conversion, the role of different catalysts in the production of biofuels, and the impacts of those fuels on society. The book brings together global experts to form a big picture of cutting-edge research in sustainable bioenergy and biofuels. It is an ideal resource for researchers, students, energy analysts and policymakers who will benefit from the book's overview of impacts and innovative needs.